Tunable spin-wave resonance and chirality control in concentric nanotori for advanced spintronic applications - Saavedra-Díaz, E (ELSEVIER, 2026)
We investigate the spin-wave dynamics in concentric magnetic nanotori through micromagnetic simulations under perpendicular pulsed magnetic fields, using the free software MuMax3. These 3D nanostructures can host homochiral and heterochiral vortex configurations, whose spin-wave spectra strongly depend on the magnetostatic coupling parameter delta. In homochiral systems, resonance modes converge as delta increases, while in heterochiral systems, they diverge. Two distinct modes are identified: one associated with the outer surfaces of the tori and another with the inner torus. A central result is the demonstration of reversible transitions between homochiral and heterochiral vortex states using oscillating magnetic fields. The switching behavior and resonance properties vary with the coupling parameter delta, revealing the system s dynamic versatility. This tunable chirality control positions concentric nanotori as promising candidates for future spintronic devices, enabling new opportunities for magnonic logic, non-volatile memory, and neuromorphic architectures. This work enhances the integration of 3D magnetic geometries with dynamic control, paving the way for applications in topological information processing and re-configurable magnetic computing.